Epoxy anticorrosive paint capable of being coated with rust and preparation method of epoxy anticorrosive paint
By using modified nanoparticles and humic acid in the coating, the problem of weak impact resistance when epoxy resin coating is combined with rust is solved, and higher impact resistance and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510149611.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-11
AI Technical Summary
During the process of epoxy resin-type coatings penetration and rust, solid nanoparticles are difficult to disperse into the rust, resulting in weak impact resistance of the paint film and difficult to resist corrosion for a long time.
By adding modified nanoparticles to the coating, the nanoparticles and rust are combined to form a mutually supportive structure, and humic acid is used as a migration enhancer to promote the nanoparticles to enter the rust and form a stronger complex.
It improves the impact resistance and corrosion resistance of the paint film, enhances the degree of bonding between rust and nanoparticles, and forms a tighter solid form.
Smart Images

Figure CN119912832A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to an epoxy anti-corrosion coating capable of being coated with rust and a preparation method thereof. Background Art
[0002] Rust coating can be directly applied on the rusted steel surface to play a role in corrosion inhibition. Applying it on the metal surface with residual rust can stabilize, passivate or transform the rust, turning the active rust into harmless substances, so as to achieve the dual role of rust prevention and protection. Rust coating is divided into conversion type, stabilization type and penetration type according to the type of raw materials.
[0003] The first is the conversion type rust-bearing paint, which uses inorganic acid or phosphoric acid to convert rust into harmless, insoluble complexes and chelates. The complexes and chelates are fixed on the basic surface of steel through the adhesion of film-forming substances. However, it is difficult to control the amount of conversion liquid for steel surfaces with uneven rust layer thickness. When the amount is small, the conversion is incomplete; when the amount is large, excessive phosphoric acid will corrode the metal itself and release hydrogen, affecting the adhesion of the coating to the metal. Its adhesion is generally lower than that of stable and penetrating coatings. The second type is the stable rust-bearing paint, which relies on zinc chromate, zinc phosphate, etc. to make rust form insoluble complexes and stable iron oxides, passivate the metal and achieve the purpose of stable corrosion. However, it does not contain organic acids, inorganic acids and other conversion agents, has little effect on rust, and stabilizes rust slowly. It is impossible to use anti-rust pigments and corrosion inhibitors to convert all rust into stable iron oxide. There are still conditions for further rusting, and the rust layer of the coating cannot be too thick. The third type is penetrating rust-resistant paint, which is a low-viscosity, high-solid content, solid content>52%, and highly permeable rust-resistant paint. It uses the wetting and penetration of the paint on loose rust to divide and surround the rust in the paint, making it inactive and preventing further development of rust. At the same time, it also uses the effect of special pigments to passivate or transform harmful iron compounds in the rust layer into stable and harmless substances. However, the disadvantage is that it must have sufficient penetrating ability to penetrate the entire loose rust layer and make the rust layer bonded to form a continuous closed coating. The rust-resistant paint must also have sufficient reactivity to the rust layer, otherwise the effect will be poor.
[0004] Therefore, the prior art mostly uses phytic acid or tannic acid or substances with phenolic hydroxyl groups to cross-link with resin to penetrate and coat the rust, thereby forming isolation and corrosion protection. However, the impact resistance of epoxy resin is poor. After combining with loose rust, moisture and oxygen are present in the formed paint film, and the impact resistance of the paint film becomes poor, which is easily damaged by side scratches. Therefore, when solid particles are used to increase its wear resistance, it is found that nano solid particles are difficult to migrate into the interior of the rust, and it is difficult to achieve good extension after modification, and they cannot be well combined in the rust to form a relatively strong complex. Summary of the invention
[0005] In order to solve the problem that during the penetration and bonding process of epoxy resin type paint and rust, solid nanoparticles are difficult to disperse into the rust to form a uniform hard structure, resulting in weak impact resistance of the paint film and difficulty in long-term corrosion protection.
[0006] The present invention provides an epoxy anti-corrosion coating capable of being coated with rust and a preparation method thereof. The technical scheme of the epoxy anti-corrosion coating is as follows:
[0007] An epoxy anticorrosive coating capable of being coated with rust comprises an epoxy component A and a curing component B, wherein the epoxy component A is composed of 30-50 parts of epoxy resin, 10-15 parts of modified nanofiller, 1-2 parts of migration enhancer, 6-8 parts of diluent and 8-12 parts of fumaric acid in parts by weight; wherein the curing component B is composed of 20-30 parts of ethyl acetate, 3-8 parts of rust converter, 2-5 parts of surfactant and 5-10 parts of penetrant in parts by weight;
[0008] The preparation method of the modified nano filler is as follows:
[0009] A1. Dissolve carboxymethyl cellulose and gallic acid in water to obtain a cross-linking solution;
[0010] A2, placing the nanoparticles in water, and adjusting the pH with an alkali solution to obtain a first dispersion of the nanoparticles;
[0011] A3, mixing diethylene glycol phthalate diacrylate with water to obtain a modified treatment solution;
[0012] A4, adding the modified treatment liquid dropwise to the first dispersion of nanoparticles, centrifugally separating to obtain modified silica, dispersing the modified nanoparticles in water to form a second dispersion of silica, adding the crosslinking liquid dropwise to the second dispersion of silica, and centrifugally separating to obtain a modified nanofiller;
[0013] The migration enhancer is humic acid.
[0014] The present application adds nanoparticles to the coating, utilizes the mutual combination of the nanoparticles and rust, forms a mutually supporting structure with the cross-linked resin skeleton, utilizes the higher surface energy of the nanoparticles, allows the rust to react with functional groups during the penetration process, thereby reducing the surface energy of the nanoparticles, thereby promoting the aggregation between the nanoparticles and the rust molecules, achieving agglomeration, and then reducing the loose structure, forming a harder and more compact solid form, thereby having higher impact resistance, increasing the anti-corrosion ability, and protecting the underlying metal.
[0015] The present application also utilizes humic acid as a migration enhancer. It is found in the examples that the addition of humic acid can promote the migration ability of nanoparticles combined with diethylene glycol diacrylate phthalate, thereby allowing the negatively charged solid nanoparticles that are difficult to enter the rust to enter the rust interlayer and disperse more evenly, and the nanoparticles are more and more tightly combined with the underlying rust. The role of diethylene glycol diacrylate phthalate is to produce ionization effect to generate quaternary ammonium cations, which rely on the interaction of charges to adsorb on the surface of nanoparticles, thereby improving the compatibility of nanoparticles and thus compounding with carboxymethyl cellulose. The role of humic acid is to reduce the interaction between nanoparticles and negatively charged rust through electrostatic repulsion and steric competition, thereby improving the migration ability of nanoparticles, thereby improving the degree of combination between rust and nanoparticles, and increasing the impact resistance of the paint film surface.
[0016] Preferably, the diluent in the epoxy component A is butyl glycidyl ether or 1,4-butanediol diglycidyl ether.
[0017] Preferably, the rust conversion agent in the curing component B is tannic acid or phytic acid, the surfactant is sodium dodecylbenzenesulfonate or dioctyl sodium sulfosuccinate, and the penetrant is cyclohexanone.
[0018] In the present application, the nanoparticles aggregate the rust molecules to form more aggregated hard particles, and then the tannic acid and phytic acid form a tougher surface paint film with these hard particles, which are connected together with a large skeleton to form a second layer structure for corrosion protection. The presence of the penetrant cyclohexanone makes it easier for the nanoparticles to enter the interior of the rust.
[0019] Preferably, the nanoparticles are silicon dioxide or titanium dioxide, and the particle size of the nanoparticles is 10-40 nm.
[0020] Nano-silicon dioxide increases the aggregation of molecules in rust, and titanium dioxide increases the weather resistance of the material, making it more resistant.
[0021] Preferably, the mass ratio of carboxymethyl cellulose to gallic acid in step A1 and the mass ratio of nanoparticles in step A2 is 4-6:3-4:1-3.
[0022] The gallic acid of the present application can aggregate more iron molecules in a unit space to form a larger complex or chelate, thereby stabilizing a solid substance.
[0023] Preferably, in step A3, the volume ratio of diethylene glycol phthalate diacrylate to water is 4:10-15, and the solid-liquid ratio of diethylene glycol phthalate diacrylate to the nano-silica is 1-3 g:16 mL.
[0024] The present application found in the examples that a better migration effect can be achieved by combining a specific diethylene glycol phthalate diacrylate with nano-silica, and that too much or too little diethylene glycol phthalate diacrylate will reduce the migration ability of nanoparticles.
[0025] Preferably, in step A4, the modified dispersion and the first silica dispersion are further subjected to ultrasonic treatment before centrifugal separation, with the ultrasonic power being 800-1200 W and the ultrasonic time being 20-35 min.
[0026] The present application also provides a method for preparing an epoxy anti-corrosion coating that can be coated with rust, and the specific preparation steps of the preparation method are as follows:
[0027] S1. Mixing the epoxy resin and the diluent, then adding the modified nanofiller to homogenize and disperse, to obtain a homogenous liquid, then dropping the migration enhancer and fumaric acid into the homogenous liquid, stirring with a stirring rod during the dropping process, to obtain epoxy component A;
[0028] S2, placing a rust conversion agent and a surfactant in ethyl acetate and homogeneously mixing them, and then adding a penetrant and stirring to obtain a curing component B;
[0029] S3, mixing the epoxy component A and the curing component B to obtain an epoxy anti-corrosion coating.
[0030] Preferably, the homogenizing and dispersing operations in S1 are magnetic stirring and ultrasonic treatment, the ultrasonic power is 1200 W, the ultrasonic treatment time is 15 min, and the number of ultrasonic treatments is 2 times.
[0031] The rust-coatable epoxy anti-corrosion coating prepared in the present application can be applied to metal surfaces with a rust layer thickness of less than 1 mm.
[0032] The beneficial effects of the present invention are as follows:
[0033] The present application modifies the nanoparticles, which can enhance the aggregation and hardness of the rust complex, enhance the compactness of the paint film, and provide a greater density, higher impact resistance and corrosion resistance.
[0034] By using diethylene glycol phthalate diacrylate to modify nano-silica, the binding ability and aggregation degree of nano-silica to rust are enhanced, and hard particles with higher density are obtained. The ability to withstand external scratches is improved, the coating is not easily lost, and the corrosion resistance is improved.
[0035] The use of humic acid competes for the electrostatic repulsion and steric hindrance between nanoparticles and rust, thereby facilitating the migration of nanoparticles and increasing the number of deep rust and surface nanoparticles combined, resulting in stronger binding energy and better corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a trend diagram of the impact resistance of the embodiments of the present invention and the comparative examples.
[0037] Figure 2 It is a comparison chart of the anti-corrosion performance of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0038] The following will refer to the attached Figure 1 to Figure 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0039] Preparation Example 1
[0040] Preparation of modified nanofillers
[0041] A1. Dissolve 25 g of carboxymethyl cellulose and 18 g of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0042] A2, placing 10 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0043] A3, 80 mL of diethylene glycol phthalate diacrylate was mixed with 250 mL of water to obtain a modified treatment solution;
[0044] A4. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 1000 W for 30 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, add the cross-linking liquid dropwise into the second dispersion of silica, and centrifuge to obtain the modified nanofiller.
[0045] Preparation Example 2
[0046] Preparation of modified nanofillers
[0047] A1. Dissolve 20 g of carboxymethyl cellulose and 15 gg of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0048] A2, placing 5 g of titanium dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0049] A3, 80 mL of diethylene glycol phthalate diacrylate was mixed with 200 mL of water to obtain a modified treatment solution;
[0050] A4. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 800 W for 20 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, add the cross-linking liquid dropwise into the second dispersion of silica, and centrifuge to obtain the modified nanofiller.
[0051] Preparation Example 3
[0052] Preparation of modified nanofillers
[0053] A1. Dissolve 30 g of carboxymethyl cellulose and 20 g of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0054] A2, placing 15 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0055] A3, 80 mL of diethylene glycol phthalate diacrylate was mixed with 300 mL of water to obtain a modified treatment solution;
[0056] A4. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 1200 W for 35 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, add the cross-linking liquid dropwise into the second dispersion of silica, and centrifuge to obtain the modified nanofiller.
[0057] Preparation Example 4 - Nanoparticles not treated with diethylene glycol phthalate diacrylate
[0058] Preparation of modified nanofillers
[0059] A1. Dissolve 25 g of carboxymethyl cellulose and 18 g of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0060] A2, placing 10 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0061] A3. Add the first dispersion of nanoparticles dropwise into the cross-linking solution, and centrifuge to obtain a modified nanofiller.
[0062] Preparation Example 5 - Excessive use of diethylene glycol phthalate diacrylate to react with nanoparticles
[0063] Preparation of modified nanofillers
[0064] A1. Dissolve 25 g of carboxymethyl cellulose and 18 g of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0065] A2, placing 10 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0066] A3, 250 mL of diethylene glycol phthalate diacrylate was mixed with 250 mL of water to obtain a modified treatment solution;
[0067] A4. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 1000 W for 30 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, add the cross-linking liquid dropwise into the second dispersion of silica, and centrifuge to obtain the modified nanofiller.
[0068] Preparation Example 6 - Using too little diethylene glycol phthalate to react with nanoparticles
[0069] Preparation of modified nanofillers
[0070] A1. Dissolve 25 g of carboxymethyl cellulose and 18 g of gallic acid in 1000 mL of water to obtain a cross-linking solution;
[0071] A2, placing 10 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjusting the pH to 10 with a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0072] A3, 25 mL of diethylene glycol phthalate diacrylate was mixed with 250 mL of water to obtain a modified treatment solution;
[0073] A4. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 1000 W for 30 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, add the cross-linking liquid dropwise into the second dispersion of silica, and centrifuge to obtain the modified nanofiller.
[0074] Preparation Example 7 - Nanoparticles not treated with crosslinking solution
[0075] Preparation of modified nanofillers
[0076] A1. Place 10 g of silicon dioxide with a particle size of 10-40 nm in 1200 mL of water, and adjust the pH to 10 using a sodium hydroxide solution to obtain a first dispersion of nanoparticles;
[0077] A2, 80 mL of diethylene glycol phthalate diacrylate was mixed with 250 mL of water to obtain a modified treatment solution;
[0078] A3. Add the modified treatment liquid dropwise into the first dispersion of nanoparticles, treat with an ultrasonic processor with a power of 1000 W for 30 minutes, centrifuge to obtain modified silica, then disperse the modified nanoparticles in water to form a second dispersion of silica, and centrifuge to obtain nanofiller.
[0079] Example 1
[0080] An epoxy anticorrosive coating capable of being painted with rust
[0081] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 13 parts of the modified nanofiller in Preparation Example 1, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time each time is 15 minutes to obtain a homogenous liquid, and then add 1.5 parts of humic acid and 10 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0082] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0083] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0084] Example 2
[0085] An epoxy anticorrosive coating capable of being painted with rust
[0086] S1. Mix 30 parts of epoxy resin and 6 parts of 1,4-butanediol diglycidyl ether by weight, then add 10 parts of the modified nanofiller in Preparation Example 2, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time each time is 15 minutes to obtain a homogenous liquid, and then drop 1 part of humic acid and 8 parts of fumaric acid into the homogenous liquid, stir with a stirring rod during the dropping process, and obtain epoxy component A;
[0087] S2, 3 parts of tannic acid and 2 parts of dioctyl sodium sulfosuccinate are placed in 20 parts of ethyl acetate and homogeneously mixed, and then 5 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0088] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0089] Example 3
[0090] An epoxy anticorrosive coating capable of being painted with rust
[0091] S1. Mix 50 parts of epoxy resin and 8 parts of butyl glycidyl ether by weight, then add 15 parts of the modified nanofiller in Preparation Example 3, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time is 15 minutes each time to obtain a homogenous liquid, and then add 2 parts of humic acid and 12 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0092] S2, 8 parts of phytic acid and 5 parts of dioctyl sodium sulfosuccinate are placed in 30 parts of ethyl acetate and homogeneously mixed, and then 10 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0093] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0094] Comparative Example 1
[0095] An epoxy anticorrosive coating capable of being painted with rust
[0096] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 12 parts of the modified nanofiller in Preparation Example 4, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time is 15 minutes each time to obtain a homogenous liquid, and then add 1.5 parts of humic acid and 10 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0097] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0098] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0099] Comparative Example 2
[0100] An epoxy anticorrosive coating capable of being painted with rust
[0101] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 12 parts of the modified nanofiller in Preparation Example 5, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time is 15 minutes each time to obtain a homogenous liquid, and then add 1.5 parts of humic acid and 10 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0102] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0103] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0104] Comparative Example 3
[0105] An epoxy anticorrosive coating capable of being painted with rust
[0106] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 12 parts of the modified nanofiller in Preparation Example 6, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time each time is 15 minutes to obtain a homogenous liquid, and then add 1.5 parts of humic acid and 10 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0107] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0108] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0109] Comparative Example 4
[0110] An epoxy anticorrosive coating capable of being painted with rust
[0111] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 12 parts of the modified nanofiller in Preparation Example 7, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time each time is 15 minutes to obtain a homogenous liquid, and then add 1.5 parts of humic acid and 10 parts of fumaric acid dropwise to the homogenous liquid, and stir with a stirring rod during the dropping process to obtain epoxy component A;
[0112] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0113] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0114] Comparative Example 5 - No Humic Acid Added
[0115] An epoxy anticorrosive coating capable of being painted with rust
[0116] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, then add 12 parts of the modified nanofiller in Preparation Example 1, perform ultrasonic treatment twice after magnetic stirring, the ultrasonic power is 1200 W, and the ultrasonic treatment time each time is 15 minutes to obtain a homogeneous liquid, and then add 10 parts of fumaric acid dropwise into the homogeneous liquid, stirring with a stirring rod during the dropping process to obtain epoxy component A;
[0117] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0118] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0119] Comparative Example 6 - No Nanoparticles Used
[0120] An epoxy anticorrosive coating capable of being painted with rust
[0121] S1. Mix 40 parts of epoxy resin and 7 parts of butyl glycidyl ether by weight, and then drop 1.5 parts of humic acid and 10 parts of fumaric acid into the homogenized liquid, stirring with a stirring rod during the dropping process to obtain epoxy component A;
[0122] S2, 5 parts of phytic acid and 4 parts of sodium dodecylbenzene sulfonate are placed in 25 parts of ethyl acetate and homogeneously mixed, and then 8 parts of cyclohexanone are added and stirred to obtain a curing component B;
[0123] S3. Mix the epoxy component A prepared in the above steps with the curing component B to obtain an epoxy anti-corrosion coating.
[0124] Experiments and data
[0125] The epoxy anticorrosion coatings prepared in the above examples and comparative examples were tested for anticorrosion performance and impact resistance, and the testing method was as follows:
[0126] Impact resistance test: The paint film surface is tested for impact force according to the test method specified in ISO 6272-2:2002. The unit is cm. The paint film does not fall off or crack under this impact height.
[0127] Anti-corrosion test: The anti-corrosion performance of the paint film was tested according to the test standard specified in JG / T 224-2007. After 1000h salt spray test, there was no blistering or falling off.
[0128] The anti-corrosion performance of the paint film is tested by rubbing the surface.
[0129] The test results are shown in Table 1 below:
[0130] Table 1
[0131]
[0132] The impact resistance of the above embodiments and comparative examples is plotted as follows: Figure 1 As shown; the anti-corrosion performance is compared by drawing a bar graph, such as Figure 2 shown.
[0133] analyze
[0134] According to the data in Table 1 of Examples 1 to 3, the rust-resistant epoxy anti-corrosion coating prepared in the present application has strong impact resistance, can effectively prevent the paint film from falling off, has excellent anti-corrosion performance, and has strong strength.
[0135] According to the experimental data of Comparative Example 1 in Table 1, it can be seen that the epoxy anti-corrosion coating prepared in Comparative Example 1 has poor impact resistance, and its salt spray corrosion resistance decreases after friction. Comparative Example 1 does not use diethylene glycol phthalate diacrylate to treat the nanoparticles. It can be seen that diethylene glycol phthalate diacrylate can change the surface energy of the nanoparticles, increase its connection reaction with carboxymethyl cellulose, and enhance the migration ability of the nanoparticles.
[0136] According to the experimental data of Comparative Examples 2 and 3, the impact resistance of Comparative Examples 2 and 3 decreased significantly, and the anti-corrosion performance decreased after friction, while Comparative Example 3 decreased the most and Comparative Example 2 decreased slightly. It can be seen that an appropriate amount of diethylene glycol phthalate diacrylate can effectively enhance the ability of nanoparticles to migrate inside the rust, and then combine with more rust molecules to form denser hard particles, thereby enhancing the anti-corrosion performance.
[0137] According to the experimental data of Comparative Example 4, the impact resistance of Comparative Example 4 is poor and the initial corrosion resistance is very low, which proves that the connection between carboxymethyl cellulose and gallic acid in the cross-linking liquid can effectively enhance the ability of nanoparticles to aggregate substances and form a denser corrosion protection layer.
[0138] According to the experimental data of Comparative Example 5, the impact resistance of Comparative Example 5 is poor, and its anti-corrosion ability also decreases to a certain extent after friction. It can be seen that humic acid can effectively increase the performance of nanoparticle migration by occupying electrostatic repulsion and steric hindrance, so that the nanoparticles can be more deeply connected to the innermost layer of rust for complexation and cross-linking, thereby enhancing its adhesion and further enhancing the anti-corrosion performance.
[0139] According to the experimental data of Comparative Example 6, Comparative Example 6 did not use nanoparticles, and its impact resistance was the worst. It was most likely to fall off in the case of a thick rust layer, and its corrosion resistance was also the lowest. It can be seen that the presence of nanoparticles has the greatest impact on the impact resistance, mainly affecting the presence of the paint film, thereby affecting the adhesion performance of the paint film, thereby improving the corrosion resistance of the paint film.
[0140] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. An epoxy anti-corrosion coating that can be painted with rust, characterized in that: The invention comprises an epoxy component A and a curing component B, wherein the epoxy component A is composed of 30-50 parts of epoxy resin, 10-15 parts of modified nanofiller, 1-2 parts of migration enhancer, 6-8 parts of diluent and 8-12 parts of fumaric acid by weight; The curing component B is composed of 20-30 parts of ethyl acetate, 3-8 parts of rust converter, 2-5 parts of surfactant and 5-10 parts of penetrant by weight; The preparation method of the modified nano filler is as follows: A1. Dissolve carboxymethyl cellulose and gallic acid in water to obtain a cross-linking solution; A2, placing the nanoparticles in water, and adjusting the pH with an alkali solution to obtain a first dispersion of the nanoparticles; A3, mixing diethylene glycol phthalate diacrylate with water to obtain a modified treatment solution; A4, adding the modified treatment liquid dropwise to the first dispersion of nanoparticles, centrifugally separating to obtain modified silica, dispersing the modified nanoparticles in water to form a second dispersion of silica, adding the crosslinking liquid dropwise to the second dispersion of silica, and centrifugally separating to obtain a modified nanofiller; The migration enhancer is humic acid.
2. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: The diluent in the epoxy component A is butyl glycidyl ether or 1,4-butanediol diglycidyl ether.
3. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: The rust conversion agent in the curing component B is tannic acid or phytic acid, the surfactant is sodium dodecylbenzene sulfonate or dioctyl sodium sulfosuccinate, and the penetrant is cyclohexanone.
4. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: The nanoparticles are silicon dioxide or titanium dioxide, and the particle size of the nanoparticles is 10-40 nm.
5. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: The mass ratio of carboxymethyl cellulose to gallic acid in step A1 and the mass ratio of nanoparticles in step A2 is 4-6:3-4:1-3.
6. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: In the step A3, the volume ratio of diethylene glycol phthalate diacrylate to water is 4:10-15, and the solid-liquid ratio of the diethylene glycol phthalate diacrylate to the nano-silica is 1-3 g:16 mL.
7. The rust-resistant epoxy anticorrosive coating according to claim 1, characterized in that: In the step A4, the modified dispersion and the first silica dispersion need to be ultrasonically treated before centrifugal separation, with an ultrasonic power of 800-1200 W and an ultrasonic time of 20-35 min.
8. The method for preparing a rust-proof epoxy anticorrosive coating according to any one of claims 1 to 7, characterized in that: The specific preparation steps of the preparation method are as follows: S1. Mixing the epoxy resin and the diluent, then adding the modified nanofiller to homogenize and disperse, to obtain a homogenous liquid, then dropping the migration enhancer and fumaric acid into the homogenous liquid, stirring with a stirring rod during the dropping process, to obtain epoxy component A; S2, placing a rust conversion agent and a surfactant in ethyl acetate and homogeneously mixing them, and then adding a penetrant and stirring to obtain a curing component B; S3, mixing the epoxy component A and the curing component B to obtain an epoxy anti-corrosion coating.
9. The rust-resistant epoxy anticorrosive coating and preparation method thereof according to claim 8, characterized in that: The homogenous dispersion operation in S1 is magnetic stirring and ultrasonic treatment, the ultrasonic power is 1200 W, the ultrasonic treatment time is 15 min, and the number of ultrasonic treatments is 2 times.
10. Use of the rust-coatable epoxy anticorrosive paint as claimed in any one of claims 1 to 7 on a metal surface with a rust layer thickness of less than 1 mm.
Citation Information
Patent Citations
Superhydrophobic transparent waterproof membrane and preparation method thereof
CN109535785A
Water-based two-component conversion type rusty anticorrosive paint and preparation method thereof
CN111393956A
Water-borne epoxy resin, preparation process thereof and epoxy zinc-rich primer
CN113683751A
Special epoxy resin paint for inner wall of cast pipe as well as preparation and application of special epoxy resin paint
CN117070121A
Polymer with anti-corrosion and heat-insulating properties as well as preparation method and application thereof
CN117964653A